Duolingo as an Artificial Intelligence Technology-Based Learning System in English - Deden Novan Setiawan Nugraha; Ervina C M Simatupang; Puspita Sari; Hero Gunawan; Dianita Dianita; Susiyanti Rusyan (Jurnal Sinestesia, 2023)
The evolving techniques of online-based learning place a demand on learning English via technology media. An alternative for learning English is through Duolingo media. The purpose of this study is to learn how to use Duolingo media to help students learn English more effectively. A qualitative methodology and action research in the classroom design were employed in this study. This research was conducted at SMAN 11 Garut, involving 50 students. Data was obtained from the results of observations, interviews, and tests. The results of this study indicate that there is an increase in students' ability to learn English by using Duolingo media.